Ragam Riwayat dan Tafsir Kisah Sulaiman dalam Al-Dakhil Fi Al-Tafsir - Masilaturrohmah,; Moh. Jufriyadi sholeh, (Advances in Humanities and Contemporary Studies, 2021)
Many of the history of Isra>i'liyat enter the world of interpretation, especially in the verses that explain the stories of the Prophets. The story of Prophet Sulayman As is one of the stories in the Koran which in its interpretation is infused with the story of Isra>'iliyat so that it tarnishes the interpretation of the verses of the story. From there the researcher is interested in tracing these deviations in order to purify the interpretation so that it becomes clear between al-As}il and al-Dakhi>1 in the interpretation of the story of the Prophet Sulaiman As. By examining QS an-Naml: 44, QS Saba': 34, and the verses that serve as evidence of the country of Saba' in Indonesia by Fahmi Basya, Then this article makes two concluding points. First, the story that contains the history of Isra>'iliyat is found in the story of Prophet Sulaiman As and queen Balqis and the story of Prophet Sulayman As who was tested with his power. Second, the interpretation of Negeri Saba' contradicts the scientific facts of archaeologists so that the story becomes part of al-dakhi>l in the interpretation of the Koran.